Silent listeners: can preferences of eavesdropping midges predict their hosts' parasitism risk?. (29th January 2016) - Meuche, Ivonne; Keller, Alexander; Ahmad Sah, Hanyrol H.; Ahmad, Norhayati; Grafe, T. Ulmar
Lay Summary: Preferences of eavesdropping predators and parasites for certain variants of mating signals of their prey may not always directly reflect the predation or parasitism risk of their victims. Using preference tests and a linear model, we show that acoustic preferences of eavesdropping frog-biting midges can be used to predict both the parasitism rate of their anuran hosts by those midges and the risk of subsequent trypanosome infection. Abstract: Eavesdropping predators and parasites that exploit the mating signals of their prey often prefer to approach certain signal variants. However, victim finding depends on many different factors. Therefore, preferences of eavesdroppers may not always directly reflect the predation or parasitism risk of the signaler. Frog-biting midges ( Corethrella spp.) and their anuran hosts offer an excellent model system to investigate this correlation. Female Corethrella are vectors of trypanosomes in frogs and use the mating calls of their anuran hosts to localize them. We tested whether the acoustic preferences of Corethrella reflects the parasitism risk of male frogs by Corethrella and trypanosomes in the field. We conducted acoustic attraction and preference tests with Corethrella in the field and used the results of the preference tests to estimate a linear model (LM) and predict the parasitism risk of sympatric frog species by Corethrella . Our preference tests in the field showed that frog-biting midges preferred higher call rates, longer calls, a frequency around 2kHz, and sounds that were broadcast near the ground. Anuran species that were predicted by our LM to produce the most attractive signal showed the highest rates of parasitism by frog-biting midges and trypanosomes. Thus, acoustic preferences of eavesdropping Corethrella can be used to predict not only the parasitism rate of their host species by Corethrella but also the risk of subsequent trypanosome transmission.